Thermal-structural Coupling Analysis of Gearbox Casing based on UG and ANSYS Workbench - Qi Xiankun; Shao Renping; Wang Yayun (Jixie chuandong)
Combining the virtual prototyping technology,finite element analysis techniques and thermal stress analysis theory,virtual prototype model of gear casing is established by UG NX 8.0.The 3-dimensional finite element model of the gear casing is established by using the seamless links of UG and ANSYS Workbench14.5,based on the theory of finite element,thermal-structural coupling analysis is implemented to the finite element model,temperature field distribution and thermal deformation of the gear casing are obtained,and centralized positions of the thermal stress and deformation is determined,and the factors that impact the temperature field distribution and thermal deformation are obtained.Through analyzing the results of the finite element simulation,the model of the heat-structure coupling analysis can provide an important reliable analysis basis for structure design,integrated design and the thermal uniform optimization design of the gearbox that worked in the complex overloaded transmission conditions which generate large amount of heat.